Mitigating bed agglomeration in a fluidized bed gasifier operating on rice straw. (November 2020) - Nisamaneenate, Jurarat; Atong, Duangduen; Seemen, Anun; Sricharoenchaikul, Viboon
Abstract: Fluidized bed gasifier is a promising technology with respect to converting biomass to useful energy. Bed agglomeration is an operational challenge that arises during fluidized bed gasification with rice straw as raw materials. Rice straw contains high amounts of potassium and other components that may lower the melting point of ash, causing bed agglomeration. Using alternative bed materials such as alumina, in the place of silica, can mitigate this problem. In Thailand, rice straw is an agricultural by-product of the rice milling processes, produced in large quantities every year. Usually, rice straw management comprises open field burning, which releases greenhouse gases, particulate matter, and other pollutants. In this paper, the behaviors of bed agglomeration and defluidization were investigated during the fluidized bed gasification of rice straw, using silica and alumina as bed materials. The effect of the percentage ratio of silica and alumina (0:100; 25:75; 50:50; 75:25; 100:0) was examined. The operating parameters were as follows: rice straw particle size of 425– 850 μ m, reaction temperature of 700–900 °C, and equivalence ratios (ER) of 0.2 and 0.4. The results showed that the percentage ratio of silica and alumina, 0:100 at 700 °C, had extended the defluidization time of 60 min. The effect of equivalence ratio on bed agglomeration was found to be apparently heightened at a high temperature. The result of SEM/EDX analysis showed that the major elements at the linkage point of the agglomerated particle were Si, K, and Ca, with regard to any proportion of the alumina bed and temperature. In conclusion, low temperature agglomerate formation can be explained by a K 2 O-CaO-Si2 O phase diagram. The results from this investigation can be applied to biomass-fluidized bed gasification, where bed agglomeration entails a plant shutdown and is expensive in terms of maintenance.